Can Posttransarterial Chemoembolization Volumetric Oil Deposition on Computed Tomography Predict Treatment Response on Magnetic Resonance Imaging in Leiomyosarcoma Metastases to the Liver?. Issue 3 (8th May 2022) - Hazhirkarzar, Bita; Shaghaghi, Mohammadreza; Baghdadi, Azarakhsh; Ghadimi, Maryam; Ghasabeh, Mounes Aliyari; Wu, Qingxia; Tang, Hao; Khoshpouri, Pegah; Ameli, Sanaz; Habibabadi, Roya R.; Motaghi, Mina; Meyer, Christian F.; et al.
Abstract : Objective: To predict early tumor response to transarterial chemoembolization (TACE) based on volumetric oil deposition on posttreatment computed tomography (CT) in patients with leiomyosarcoma liver metastases. Methods: This retrospective lesion-by-lesion based study included 32 lesions. The volumetric percent enhancing tumor on pre-TACE and 1-month post-TACE venous phase magnetic resonance imaging (MRI), and the percent oil deposition on CT 1 day after TACE were calculated. The predicted post-TACE enhanced percentage was computed by subtracting percent oil deposition from baseline percent enhanced. Results: Mean percentage of viable tumor on pre-TACE MRI was 90.6% ± 9.3%. Mean oil deposition was calculated as 51.4% ± 26.2%. Mean percentage of measured residual tumor enhancement 1 month after TACE was 58.3% ± 27%, which correlates with predicted enhancement percentage of 43.9% ± 25.1% ( r = 0.72, P < 0.001). A threshold of 35.5% for enhancement reduction was determined to predict tumor response with an accuracy of 78.1%. Conclusion: Volumetric oil deposition on CT can predict residual enhancement on post-TACE MRI.